Doelwitbestuur: 'n Pragmatiese benadering - J. J. Murphy (South African Journal of Business Management, 1982)
– Management by objectives: A pragmatic approach This article has a dual purpose. Firstly, the advantages associated with management by objectives (MBO) are outlined and the problems commonly experienced with implementation are highlighted. This part of the article is concluded by listing the eight key points that must be considered before any organization implements MBO. Secondly, 10 steps in the MBO process are discussed. These steps are considered within the context of the planning and control systems of the company or organization. This means that the MBO process is integrated with the planning and control systems of the organization.
Keywords: 650